Influence of extracts of Stryphnodendron polyphyllum Mart. and Stryphnodendron obovatum Benth. on the cicatrisation of cutaneous wounds in rats - Lopes, G. C.; Sanches, ACC; Nakamura, C. V.; Dias, B. P.; Hernandes, L.; de Mello, JCP (Elsevier B.V., 2005)
Stem bark of the two species Stryphnodendron polyphyllum Mart. and Stryphnodendron obovatum Benth., Leguminosae, was investigated for wound healing, antibacterial and antioxidant activity. These plants contain 12 and 19% tannins in their stem bark, respectively, and are widely used in traditional medicine in Brazil. The total content of phenolics of the crude extract (CE) of Stryphnodendron obovatum was 76.95 +/- 2.98% (CV = 3.87%) and of the ethyl-acetate fraction (EAF) was 89.13 +/- 0.34% (CV = 0.38%); whereas in Stryphnodendron polyphyllum the CE phenolics content was 51.62 +/- 1.53% (CV = 2.96%) and the EAF phenolics content was 59.00 +/- 1.91% (CV = 3.24%). The tannin content of CE from Stryphnodendron obovatum [36.58 +/- 0.35% (CV = 0.98%)] was about 11% higher than in CE from Stryphnodendron polyphyllum [25.43 +/- 0.96% (CV = 3.77%)]. The difference between the species was even greater in the EAF: in Stryphnodendron obovatum the EAF phenolics content was 55.01 +/- 0.36% (CV = 0.65%), whereas in Stryphnodendron polyphyllum the content was 36.16 +/- 0.42% (CV = 1.16%). The healing effect of ointments containing 2.5% crude lyophilised extract (PCE) and 2.5% ethyl-acetate lyophilised fraction (PEA) of the stem bark of Stryphnodendron polyphyllum and Stryphnodendron obovatum was studied in cutaneous wounds of Wistar((R)) rats after 4, 7 and 10 days of treatment. Epithelial cell proliferation in the area of re-epithelialisation of the wounds was evaluated by counting the metaphases blocked by vincristine sulfate. With PCE an increase in epidermal growth was observed after 4 and 7 days of treatment with Stryphnodendron polyphyllum, and after 7 and 10 days of treatment with Stryphnodendron obovatum. Wounds treated with PEA of Stryphnodendron obovatum showed increased epidermal growth only 4 days after the treatment, for Stryphnodendron polyphyllum, epidermal growth was observed after 4 and 7 days of treatment. Both the CE and the EAF fractions of Stryphnodendron polyphyllum and Stryphnodendron obovatum showed antibacterial activity against Staphylococcus aureus with MIC values of 125 and 250 mu g/ml, respectively. Gram-negative bacteria tested were not inhibited by extracts and fractions at concentrations > 1000 mu g/ml. The antioxidant activity through reduction of the DPPH radical in TLC, confirmed the anti-radical properties of these extracts in both species. CE and EAF of both species showed a radical scavenging activity (RSA) and protected DPPH from discolouration, already at 0.032 mu g/ml. The extract from Stryphnodendron polyphyllum were more effective than those Stryphnodendron obovatum, although the former had a lower tannin content. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: Stryphnodendron obovatum; Stryphnodendron polyphyllum; epidermal proliferation; antibacterial activity; antioxidant activity; tannins